Volilna pravica tujcev s stalnim prebivališčem kot prispevek integraciji in lokalni samoupravi - Medved, Felicita (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2002)
Voting rights of foreign nationals as a contribution to integration and lokal democraty in 2002, year of municipal elections, Slovenia introduced the right of foreign nationals with permanent resident status to vote and to stand as a candidate in municipal elections, reserving passive voting right for a mayor to the nationals. Voting rights of citizens of the European Union were argued on the basis of anticipated inclusion of Slovenia in to the European Union, while at the same time extending this right to orther foreign nationals was presented as a matter of civilisation, culture and political standards of political judgement. This article attemps to comment on motivation, ambitions and goals of this amendment to the law on local elections as confronted with two political principles: the democratic idea of representative government and the principle of sovereignty of nation-states where democracz as a common rule presupposes that only nationals maz vote and stand for election. Therefore, typology of the rights according to nationality and territorial status is presented, followed by a description of political and voting rights of foreign nationals in same European countries and the European Union. Fianally, some conclusion remarks are given about consequences of the electoral reform on social integration, local self-management and development of "nominal" and "residential citizenship".
Keywords: Slovenia; Slovenija; državljanstvo; volilna pravica; tujci; local government; lokalna samouprava; občine